Mixing Digital Humanities and Applied Science Librarianship - Holly Hendrigan (Issues in Science and Technology Librarianship)
Awareness of faculty research interests is an important aspect of a subject librarian's responsibilities. This paper illustrates the potential of Voyant Tools, an application in wide use among digital humanities researchers, to reveal word patterns in the research output of applied science faculty. A corpus of recent article citations from Web of Science from two engineering departments was obtained, and the articles' title field was extracted and uploaded to the application. The exercise indicated that articles on fuel cells dominates the research output of one department, and articles on optical coherence tomography dominates the other. Both the corpus of citations and its visualizations in Voyant Tools contribute to librarians' knowledge of their departments and historical spending patterns on specialized resources. This knowledge can be used in professional practice, including collection development and instruction. As academic subject areas become increasingly complex and multidisciplinary, this paper encourages librarians to engage with Voyant Tools to better understand the specialized language and concepts of these evolving fields.